Long-acting Reversible Contraception Among Homeless Women Veterans With Chronic Health Conditions: A Retrospective Cohort Study - Gawron, Lori M; Redd, Andrew; Suo, Ying; Pettey, Warren; Turok, David K; Gundlapalli, Adi V (Medical care, 2017)
US women Veterans are at increased risk of homelessness and chronic health conditions associated with unintended pregnancy. Veterans Health Administration (VHA) provision of long-acting reversible contraception (LARC) can assist in healthy pregnancy planning. To evaluate perinatal risk factors and LARC exposure in ever-homeless women Veterans. A retrospective cohort study of women Veterans using VHA administrative data from fiscal years 2002-2015. We included 41,747 ever-homeless women Veterans age 18-44 years and 46,391 housed women Veterans matched by military service period. A subgroup of 7773 ever-homeless and 8674 matched housed women Veterans deployed in Iraq and Afghanistan [Operations Enduring Freedom/Iraqi Freedom/New Dawn (OEF/OIF/OND)] conflicts comprised a second analytic cohort. Descriptive statistics compared demographic, military, health conditions, and LARC exposure in ever-homeless versus housed women Veterans. Multivariable logistic regression explored factors associated with LARC exposure in the OEF/OIF/OND subgroup. All health conditions were significantly higher in ever-homeless versus housed Veterans: mental health disorder in 84.5% versus 48.7% (P<0.001), substance abuse in 35.8% versus 8.6% (P<0.001), and medical conditions in 74.7% versus 55.6% (P<0.001). LARC exposure among all VHA users was 9.3% in ever-homeless Veterans versus 5.4% in housed Veterans (P<0.001). LARC exposure in the OEF/OIF/OND cohort was 14.1% in ever-homeless Veterans versus 8.2% in housed Veterans (P<0.001). In the OEF/OIF/OND cohort, homelessness along Veterans with medical and mental health indicators were leading LARC exposure predictors. The VHA is successfully engaging homeless women Veterans and providing LARC access. The prevalence of perinatal risk factors in ever-homeless women Veterans highlights a need for further programmatic enhancements to improve reproductive planning.